Translation Procedures Applied in Translating Immigration Terminologies - Shanti Nilayani, Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): : September, 2020)
Translating technical terminologies that belong to special field is challenging, especially to those who are not mastering the field. In translating the immigration terminologies found in the regulations concerning immigration, the translators applied various translation procedures in order to maintain the meaning. The aim of this research is to identify the translation procedures applied in translating the immigration terminologies found in the data source. The data were collected from Undang-Undang Nomor 6 Tahun 2011 tentang Keimigrasian, Peraturan Presiden Republik Indonesia Nomor 104 Tahun 2015 tentang Perubahan Atas Peraturan Presiden Nomor 69 Tahun 2015 tentang Bebas Visa Kunjungan, along with their translations . Qualitative research approach is applied in this writing. The theory used to analyze the data is the theory of translation proposed by Vinay and Darbelnet. The result of the research showed that in translating the immigration terminologies found in the data source, the translator applied 5 (five) out of 7 (seven) translation procedures. These 5 (five) procedures are borrowing, calque, literal, transposition, and modulation. The other 2 (two) translation procedures that were not applied are equivalence and adaptation.